The arts and section-32 of the 1984 Finance Act - O'Hagan, John W.; Duffy, Christopher T. (Economic & Social Studies, 1988)
Research on the economics of the arts has grown enormously in the last decade (see O'Hagan and Duffy, 1987). One area which has received particular attention is that of tax concessions to the arts (see, for example, Feld, O'Hare and Schuster, 1983; Hochman and Rodgers, 1986; Netzer, 1978; and Schuster, 1985 and 1986). Outside the United States, however, there has been little published research on this topic and the purpose of this short paper is to redress somewhat this situation by examining the 1984 Finance Act as it applies to the arts in Ireland.
Keywords: Arts - Economics; Arts funding - Ireland